ДОСЛІДЖЕННЯ ВПЛИВУ КОМПЕНСУВАЛЬНИХ УСТАНОВОК НА ДОДАТКОВІ ВТРАТИ АКТИВНОЇ ПОТУЖНОСТІ ВІД НЕСИМЕТРІЇ РЕЖИМУ - Терешкевич, Л. Б.; Червінська, Т.М.; Бандура, І.О. (Інститут електродинаміки НАН України, Київ, 2023)
Investigation of symmetric as well as asymmetric capacitors battery influence on additional watt losses of mode asymmetry in grids of power supply organizations and power consumers are realized. References 3, tables 2, figures 5.